The Impact of I’rab Forms on the Diversity of Meaning in the Qur’an - DEMİRDÖVEN, Necla Yasdıman (Journal of Ecohumanism, 2024)
This study investigates the role of i’rab in conveying meaning in the Qur’an and how different i’rab interpretations can lead to changes in meaning. It also examines how scholars in Theology faculties and Islamic Education institutions in Turkiye evaluate the impact of i’rab diversity on the meaning of the Qur’an in their theses and articles. The introduction addresses the factors causing i’rab diversity, and the main section provides examples of how i’rab diversity affects Qur’anic meanings. Although we must limit our examples due to the scope of the article, a general idea of the situation will emerge, highlighting how different uses of i’rab affect the understanding of the Qur’an. The accurate learning and teaching of i’rab and its impact on understanding the Qur’an are among the probable outcomes of our research. Understanding the different i’rab forms of a word or sentence helps us better grasp the original meaning and intent of the text. In summary, this study demonstrates that the Qur’an can contain different meanings and interpretations, highlighting the role of i’rab. Thus, the richness and depth of the text will be recognized.